Penggunaan Media Puzzle sebagai Sarana Pengembangan Kognitif dan Sosial Anak pada KB Arga Mulya - Puji Rahayu; Itsnaini Muslimati Alwi (ARZUSIN, 2026)
Early childhood education requires learning strategies that are appropriate to children’s developmental characteristics, but learning practices in playgroups are still often limited in the use of varied and engaging media, so the stimulation of children’s cognitive and social development has not been optimal. This study aimed to examine the use of puzzle media as a learning strategy and its implications for the cognitive and social development of early childhood at Arga Mulya Playgroup. This study used a qualitative approach with a case study design. The research subjects consisted of 10 children and a classroom teacher selected through purposive sampling. Data were collected through observation, interviews, and documentation, and were then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through source and technique triangulation. The results showed that the use of puzzle media had a positive impact on the learning process and children’s development. Children showed increased learning interest, activeness, and ability to concentrate for longer periods. Children’s cognitive abilities also developed, particularly in recognizing shapes and colors, thinking logically, and solving simple problems. In addition, children showed improvement in social and character aspects, such as carefulness, patience, and perseverance. The conclusion of this study confirms that puzzle media can serve as an effective alternative learning strategy to support the cognitive and social development of early childhood in playgroups.